Evaluation of the genetic resistance status to classical and atypicalscrapie in Karacabey merino rams - (:unkn) unknown (My University, 2015)
0

Scrapie, the oldest prion disease of sheep, has two types: classical and atypical scrapie. It was determined that some nucleotide polymorphisms in the PrP coding gene have affected classical and atypical scrapie susceptibility. Consequently, EU member states have established breeding programs aiming to increase genetic resistance of their flocks to classical scrapie. These breeding programs have primarily been implemented in economically important breeds. Thus, we investigated classical and atypical scrapie related PrP genotypes of the Karacabey merino breed, which is of great economic importance in western regions of Turkey. In relation to classical scrapie, three alleles (ARR, ARQ, and VRQ) and five genotypes (ARR/ARR, ARR/ARQ, ARQ/ARQ, ARR/VRQ, and ARQ/VRQ) were identified. Frequencies were found to be 0.280, 0.677, and 0.043 for the alleles and 0.086, 0.376, 0.452, 0.011, and 0.075 for the genotypes, respectively. In terms of atypical scrapie, four alleles (ALRR, ALRQ, AFRQ, and VLRQ) and eight genotypes (ALRR/ALRR, ALRR/AFRQ, ALRR/ALRQ, ALRQ/AFRQ, ALRQ/ALRQ, VLRQ/ALRR, VLRQ/ALRQ, and VLRQ/AFRQ) were identified. Frequencies were found to be 0.272, 0.636, 0.049, and 0.043 for the alleles and 0.076, 0.033, 0.348, 0.043, 0.413, 0.011, 0.054, and 0.022 for the genotypes, respectively. Three nonsynonymous and two silent additional polymorphisms were also determined along with the PrP coding gene.
Keywords: Ziraat Mühendisliği